2018
DOI: 10.3389/fphys.2018.01691
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Coupling Remains Intact During Incremental Ascent to High Altitude (4240 m) in Acclimatized Healthy Volunteers

Abstract: Neurovascular coupling (NVC) is the temporal link between neuronal metabolic activity and regional cerebral blood flow (CBF), supporting adequate delivery of nutrients. Exposure to high altitude (HA) imposes several stressors, including hypoxia and hypocapnia, which modulate cerebrovascular tone in an antagonistic fashion. Whether these contrasting stressors and subsequent adaptations affect NVC during incremental ascent to HA is unclear. The aim of this study was to assess whether incremental ascent to HA inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
3
12
1
Order By: Relevance
“…The reductions observed in both end‐tidal CO 2 and SnormalpO2 are similar to those observed previously with identical ascent profiles (e.g. Bruce et al., 2018; Leacy et al., 2018; Zouboules et al., 2018). The changes observed in the cardiorespiratory system during exposure to high altitude are a result of the HVR, in part.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reductions observed in both end‐tidal CO 2 and SnormalpO2 are similar to those observed previously with identical ascent profiles (e.g. Bruce et al., 2018; Leacy et al., 2018; Zouboules et al., 2018). The changes observed in the cardiorespiratory system during exposure to high altitude are a result of the HVR, in part.…”
Section: Discussionsupporting
confidence: 89%
“…Second, the acid-base status of our participants was not recorded during ascent and descent. However, in a previous study by our group incorporating an identical ascent profile we showed that arterial pH is remarkably stable during incremental ascent up to 5160 m (Leacy et al, 2018;Zouboules et al, 2018) Lastly, the time course of ascent and descent profiles was not uniform. Ascent from 1400 to 5160 m was achieved over 11 days.…”
Section: Methodological Considerationsmentioning
confidence: 64%
See 1 more Smart Citation
“…During the first few days of exposure to HA, resting HR and vascular tone increase as a consequence of acute hypobaric hypoxia by stimulation of peripheral chemoreceptors, increasing sympathetic nervous system activity (Bärtsch & Gibbs, 2007;Hainsworth, Drinkhill, & Rivera-Chira, 2007). However, in the present investigation, resting HR and MAP were unchanged with ascent, most likely a response due to a relatively slow ascent profile with regular rest days enabling proper acclimatization to occur, as well as the vasodilatory effects of systemic hypoxia (Lafave et al, 2019;Leacy et al, 2018).…”
Section: Diving Bradycardia With Ascentcontrasting
confidence: 59%
“…Indeed, hyperventilation‐induced hypocapnia was previously shown to suppress the neurovascular coupling response in healthy humans (Szabo et al., ). During hypocapnia, it is unclear whether the decreased partial pressure of carbon dioxide or the resultant alkalosis serves as the primary stimulus, but interestingly, neurovascular coupling was found to be intact in acclimatized healthy participants at high altitude, in whom profound hypocapnia was compensated over the course of several days by renal clearance of bicarbonate, restoring near‐normal pH (Leacy et al., ). Renal compensation would not have occurred in the study by Friend et al.…”
mentioning
confidence: 99%